2015
DOI: 10.32421/juri.v22i2.104
|View full text |Cite
|
Sign up to set email alerts
|

Success of Percutaneous Nephrolithotomy: Comparing Spinal Anesthesia With General Anesthesia

Abstract: Objective: The purpose of this study compared the outcome of PCNL under general and spinal anesthesia for the outcome. Material & Methods: PCNL had been performed from 2000 until 2011 with total 760 PCNL divided into 220 PCNL using general anesthesia (Group A) and the remaining 540 PCNL using spinal anesthesia (Group B) The data of both groups were evaluated with Chi square test, and Mann-Whitney test. Result: Stone free rate in Group A was 71.37% similar with Group B 72.97% (p > 0.05). Spinal anesthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…compared 220 PCNL procedures using general anesthesia and 540 PCNL using spinal anesthesia. They found the stone-free rate in the general anesthesia group was 71.37%, similar to the spinal anesthesia group 72.97% (p > 0.05) 35 . Kuzgunbay et al 36 and Tangpaitoon et al 37 also found that combined spinal-regional anesthesia is a feasible technique in PCNL operations because the efficacy and safety were not affected compared to PCNL with general anesthesia.…”
Section: Discussionmentioning
confidence: 69%
“…compared 220 PCNL procedures using general anesthesia and 540 PCNL using spinal anesthesia. They found the stone-free rate in the general anesthesia group was 71.37%, similar to the spinal anesthesia group 72.97% (p > 0.05) 35 . Kuzgunbay et al 36 and Tangpaitoon et al 37 also found that combined spinal-regional anesthesia is a feasible technique in PCNL operations because the efficacy and safety were not affected compared to PCNL with general anesthesia.…”
Section: Discussionmentioning
confidence: 69%